2016
DOI: 10.1016/j.brainres.2015.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic hypothermia and targeted temperature management in traumatic brain injury: Clinical challenges for successful translation

Abstract: The use of therapeutic hypothermia (TH) and targeted temperature management (TTM) for severe traumatic brain injury (TBI) has been tested in a variety of preclinical and clinical situations. Early preclinical studies showed that mild reductions in brain temperature after moderate to severe TBI improved histopathological outcomes and reduced neurological deficits. Investigative studies have also reported that reductions in post-traumatic temperature attenuated multiple secondary injury mechanisms including exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 110 publications
0
52
0
2
Order By: Relevance
“…It is well established that dizocilpine maleate (MK-801) and hypothermia confer neuroprotection, reduce inflammatory responses, and attenuate functional deficits after brain trauma (Shapira et al, 1990; Clifton et al, 1991; Bramlett et al, 1995; Clark et al, 1996; Dixon et al, 1998; Koizumi and Povlishock, 1998; Goda et al, 2002; Han et al, 2009; Sönmez et al, 2015; Dietrich and Bramlett, 2015), but the effects of their combination is less known, especially in pediatric rats. To address this issue, Çelik and colleagues (2006) produced a TBI via a weigh drop in 17-day-old male and female rats and assigned them to normothermia (36 °C), hypothermia (32 °C), normothermia + MK-801 (0.5 mg/kg at 15 and 45 min after TBI, i.p.)…”
Section: Neurotransmitter Dysregulationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that dizocilpine maleate (MK-801) and hypothermia confer neuroprotection, reduce inflammatory responses, and attenuate functional deficits after brain trauma (Shapira et al, 1990; Clifton et al, 1991; Bramlett et al, 1995; Clark et al, 1996; Dixon et al, 1998; Koizumi and Povlishock, 1998; Goda et al, 2002; Han et al, 2009; Sönmez et al, 2015; Dietrich and Bramlett, 2015), but the effects of their combination is less known, especially in pediatric rats. To address this issue, Çelik and colleagues (2006) produced a TBI via a weigh drop in 17-day-old male and female rats and assigned them to normothermia (36 °C), hypothermia (32 °C), normothermia + MK-801 (0.5 mg/kg at 15 and 45 min after TBI, i.p.)…”
Section: Neurotransmitter Dysregulationmentioning
confidence: 99%
“…Several pre-clinical treatment approaches, including, but not limited to, anti-inflammatory and anti-oxidative strategies (Knoblach and Faden, 1998; Hall et al, 1999; Kline et al, 2004b; Bayir, 2005; Gopez et al, 2005; Wu et al, 2006; Jing et al, 2012; Anthonymuthu et al, 2015; Hellewell et al, 2015), hypothermia (Clifton et al, 1991; Bramlett et al, 1995; Clark et al, 1996; Dixon et al, 1998; Koizumi and Povlishock, 1998; Dietrich and Bramlett, 2015), exogenous administration of neurotrophins (Dixon et al, 1997a; McDermott et al, 1997; Saatman et al, 1997; Sinson et al, 1997; Carlson et al, 2014), pharmacologic agents targeting various neurotransmitter systems (Feeney et al, 1993; Temple and Hamm, 1996; Kline et al, 2000, 2002, 2010; Parton et al, 2005; Baranova et al, 2006; Cheng et al, 2008, 2015; Reid and Hamm, 2008; Bales et al, 2009; Osier and Dixon, 2015; Markos et al, 2016), neutraceuticals (Hoane et al, 2003, 2005, 2008; GĂłmez-Pinilla, 2008; Guseva et al, 2008; Kokiko-Cochran et al, 2008; Peterson et al, 2012; Agrawal et al, 2015; Vonder Haar et al, 2015), rehabilitative approaches (Hamm et al, 1996; Maegele et al, 2005; Matter et al, 2011; Cheng et al, 2012; Monaco et al, 2013, 2014; Bondi et al, 2014, 2015a,b; Griesbach et al, 2012, 2015; Kreber and Griesbach, 2016), and stem cell transplantation (Gao et al, 2006; Riess et al, 2007; Valle-Prieto and Conget, 2010; Zanier et al, 2011; De La Peña et al, 2015; Patel and Sun, 2016) have been shown to confer motor and/or cognitive benefits in research laboratories using clinically relevant experimental models (Kline and Dixon, 2001, Cernak, 2005; Morales et al, 2005; Morganti-Kossmann et al, 2010; Marklund and Hillered, 2011; Johnson et al, 2015), but few have successfully translated to the clinic (…”
Section: Introductionmentioning
confidence: 99%
“…Again, as we noted above, since HIE shares some pathologic similarities with neonatal TBI, the use of hypothermia may have some benefit in neonatal TBI. Indeed, hypothermia may benefit severe adult TBI cases, but more research is needed to translate these findings to neonatal cases [69]. In particular, adult mice exposed to hypothermia treatment improved cognitive functions by increasing neuronal plasticity [70].…”
Section: Caveats and Future Directionsmentioning
confidence: 99%
“…[59][60][61][62][63][64] Temperature management in the brain is very important after cerebral injury. 65,66 Deep hypothermia (below 30 C) appears to show no benefits for TBI while mild to moderate hypothermia (32 to 35 C) displays neuroprotective effects. 67,68 However, the neuroprotective mechanisms of hypothermia after TBI remain poorly understood.…”
Section: 34mentioning
confidence: 99%